The Effect of Low Velocity Impact Loading on Self-Compacting Concrete Reinforced with Carbon Fiber Reinforced Polymers - Abd, J.; Ahmed, I. K. (Engineering, Technology & Applied Science Research, 2021)
Self-Compacting Concrete (SCC) reduces environmental noise and has more workability. This research presents an investigation of the behavior of SCC under mechanical loading (impact loading). Two types of cement have been used to produce SCC mixtures, Ordinary Portland Cement (OPC) and Portland Limestone Cement (PLC), which reduces the emission of carbon dioxide during the manufacturing process. The mixes were reinforced with Carbon Fiber Reinforced Polymer (CFRP) which is usually used to improve the seismic performance of masonry walls, to replace lost steel reinforcements, or to increase column strength and ductility. Workability tests were carried out for fresh SCC. Prepared concrete slabs of 500×500×50mm were tested for low-velocity impact loading at ages of 28, 56, and 90 days after water curing. The results were compared with the ones of non-reinforced SCC mixes and show a significant effect on the impact resistance after the SCC was reinforced with CFRP. The strongest impact resistance was recorded for reinforcing slabs made from OPC SCC, while for the reinforced concrete slabs produced from PLC the results were less, but at a close rate.